A PROTEÇÃO DE DADOS COMO DIREITO FUNDAMENTAL INDIVIDUAL E ELEMENTO AO EXERCÍCIO DA CIDADANIA NO BRASIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This work analyzes how the advancement of technological means in the face of accelerated growth turns the individual into an agent of two worlds. It is not possible today to disconnect the real individual from the digital universe, because even if they are not present, their information is circulating 24 hours a day on servers around the world and can be used by the data owner or by third parties. By methodologically analyzing the specific literature developed on the subject and by imputing international legislation on the subject, we create a logical spiral that directs us to the center of knowledge capable of allowing us to evaluate the same topic in Brazil, but with an impartial and analytical focus on the matter. of how Brazilians' information is protected and how this threat can harm individual security, the exercise of citizenship and, in more extreme scenarios, National Security, as fragility in the management of information plays a fundamental role in access to international financing and above all, maintenance of sovereignty.